Molecular Docking to Explore the Interaction of Emodin and Piplartine with Biological Receptors of the TGF-β Signaling Pathway in Head and Neck Squamous Cell Carcinoma - Martinho, Júlia de Oliveira; Castanhole-Nunes, Márcia Maria Urbanin; Henrique, Tiago; Kawasaki-Oyama, Rosa Sayoko; Júnior, Vilson Serafim [UNESP]; Possebon, Vitória Scavacini; Pavarino, Erika Cristina; Goloni-Bertollo, Eny Maria (Bentham Science Publishers, 2025)
Introduction: Inflammation and cytokine expression play key roles in HNSCC development. TGF-β regulates multiple cancer-related processes, and natural compounds, such as emodin and piplartine, are known for their anti-cancer and anti-inflammatory effects. These effects are related to the ability to modulate molecular targets linked to the TGF-β signaling pathway. Methods: This study conducted an in silico analysis of natural compounds interacting with TGF-β pathway receptors. Six candidate receptors (LTBP1, TGF-β1, TGFβR1, SMAD2, E2F4, and EMP3) were selected based on database and literature searches. Protein and ligand models were obtained from specific databases, and molecular docking was performed using CB-Dock2. Results: Emodin showed docking scores of -7.4, -7.6, -9.0, -7.5, -6.9, and -7.0 kcal/mol with receptors LTBP1, TGF-β1, TGFβR1, SMAD2, E2F4, and EMP3, respectively. Piplartine showed lower docking scores of -6.6, -6.4, -8.2, -6.7, -6.0, and -6.0 kcal/mol, respectively. The molecular docking protocol was validated by redocking the known inhibitor to TGFβR1, resulting in a low RMSD value, confirming the reliability of CB-Dock2. Discussion: According to these in silico results, emodin exhibits higher binding affinity to TGF- β receptors than piplartine. New candidate receptors (EMP3, LTBP1, and E2F4) were identified as potential therapeutic targets in HNSCC. High EMP3 expression significantly correlates with worse patient survival, indicating its prognostic potential. Conclusion: These findings provide a promising preliminary indication of emodin as a potential modulator of targets in the TGF-β signaling pathway in HNSCC, supporting its further investigation in in vitro and in vivo models.